Active Faults in Southwestern Kathmandu Basin, Central Nepal - Saijo, Kiyoshi; Kimura, Kazuo; Dongol, Gopal; Komatsubara, Taku; Yagi, Hiroshi (Journal of Nepal Geological Society, 1995)
Two active faults running in NW-SE direction are discussed in the southwestern margin of the Kathmandu Basin. The fault morphology is expressed by isolated mounds, scarps, and depressions. The faults dislocate the colluvial slopes and terraces of the late Pleistocene. The Quaternary sediments in the vicinity of the fault zone are tilted. The field evidences suggest the downthrow of the foot wall along the southwestward dipping fault plane. The vertical rate of displacement along the fault exceeds 1.0 mm/yr. The right-lateral slip, which is characteristic of the NW-SE trending faults in the Nepal Himalaya (Nakata 1988), is not recognised in this area.